Different Rola Perceptions and Student-Teacher Relationship Characteristics, Among High School Homeroom Educators and Subject Teachers' – Results From a Qualitative Research - Gosen, Noah Bar (Wydawnictwo Naukowe UAM, 2015)
Teaching staff in Israel is expected to fulfill the role of civil and moral educators alongside their instructional roles. In order to achieve that goal, the Israeli education system has defined two distinct entities: the first is the unique position of the “mechanech kita”, or a homeroom educator, whose role is to address all aspects of the students’ lives. The second role is the subject teacher, who teaches a specific subject in various classes. Semi-constructed interviews of 14 high school teaching staff helped to shed light on the perceptions and practices concerning role definition and the teacherstudent relationship. The results show that homeroom educators emphasize a holistic view and perceive responsibility for the “whole student”. Both instructors valued a strong and consistent relationship with their students, but homeroom educators invested more time and employed more varied strategies to achieve it. Subject teachers emphasized scholastic aspects and practices. The results show that different role definitions lead to different role perceptions and student-teacher relationship characteristics. Further research concerning the implications of such differences on educational and inclusive processes within the school system. Implications concerning teachers’ professional training course should be considered as well.
Różne percepcje ról i cech relacji uczeń-nauczyciel u wychowawców klas oraz nauczycieli przedmiotu – wyniki badań jakościowych
Keywords: homeroom educators; subject teachers; role definition; role perception; student-teacher relationship; inclusive practice